A multi-objective sustainable load planning model for intermodal transportation networks with a real-life application. (November 2016) - Baykasoğlu, Adil; Subulan, Kemal
Highlights: A multi-objective, multi-mode & multi-period sustainable load planning model. Real-life application to a large-scaled international logistics company in Turkey. Various decisions like transportation mode/service type selection, outsourcing. Load allocation, transshipment operations, usage of block trains & Ro-Ro vessels. Simultaneous flows of the import and export loads on intermodal logistics network. Minimizing overall transport cost & CO2 emission, maximizing customer satisfaction. Abstract: Growing importance of intermodal transportation necessitates modeling and solving load planning problems by taking into account various complex decisions simultaneously like transportation mode/service type selection, load allocation, and outsourcing. This paper presents a mixed-integer mathematical programming model for a multi-objective, multi-mode and multi-period sustainable load planning problem by considering import/export load flows to satisfy transport demands of customers and many other related issues. Several multiple objective optimization procedures are utilized in order to handle conflicting objectives simultaneously under crisp and fuzzy decision making environments. A real-life case study is also performed to present application and usefulness of the proposed model.